Analysis of Roman Imperial coins by combined PIXE, HE-PIXE and μ-XRF. (January 2019) - Vadrucci, M.; Mazzinghi, A.; Gorghinian, A.; Picardi, L.; Ronsivalle, C.; Ruberto, C.; Chiari, M.
Abstract: Development of non-destructive or micro-invasive scientific diagnostic techniques gained an outmost importance in the field of Cultural Heritage, contributing to assess authenticity, provenience and age of the objects, as well as supplying additional information to art conservators, to accomplish suitable restoring and preservative procedures. However, each diagnostic technique has its own advantages and limitations, thus in many cases the optimal sample characterization requires a synergy between different analytical approaches. In this context, Particle Induced X-ray Emission (PIXE) and high energy (HE) PIXE with 3 MeV and 17 MeV proton beams respectively, Elastic Backscattering Spectrometry (EBS) and micro X-Ray Fluorescence (μ-XRF) techniques were applied in a multi-analytical approach to characterize the composition of the artifacts. The analysed samples were four Roman Imperial coins belonging to different periods between 41 A.D. and 4 B.C. The employed Ion Beam Analysis (IBA) and XRF provided comparable quantitative results relative to the main sample elemental composition. The obtained results vary significantly from one coin to the other, depending on the production date and place, and on the conservation conditions. Highlights: Comparison between different non-destructive scientific diagnostic techniques useful in art and cultural heritage; PIXE analysis with proton beams of two largely different energies to measure profiles from the surface of the material towards the bulk; Stratigraphic measurements for cultural heritage characterization; Quantitative determination of the alloys used for the realization of the coins.